Supporting weight management of pregnant women with overweight: Wearable Internet-of-Things intervention - Saarikko, Johanna (fi=Turun yliopisto|en=University of Turku|, 2025)
This study aimed to develop an intervention to support weight management of women with overweight during pregnancy and the postpartum period and to evaluate the feasibility of the intervention. The study was conducted in two phases: development and feasibility. The development phase included two substudies: (1) A mixed method, descriptive study examined perceptions of weight management support among maternity care professionals (n=5) and pregnant women with overweight (n=11). (2) A prospective observational study summarized the feasibility of the Wearable Internet-of-Things-based system to continuously monitor the health parameters among pregnant and postpartum women (n=20). The data collected during the development phase were used to model a weight management intervention and implementation strategies with a cocreation approach. The intervention’s core components were: (1) health technology; (2) motivational interviewing; (3) goal setting; and (4) feedback. The feasibility phase consisted of a quasi-experimental trial to assess the effectiveness of the weight management intervention in terms of improving self-efficacy in eating and physical activity and preventing gestational weight gain among pregnant women with overweight (n=54). Fidelity, acceptability, and adherence to the intervention were also evaluated. The results showed that the intervention had no effect on a change in self-efficacy or weight gain. However, the importance of recommended gestational weight gain on better postpartum weight management was highlighted. In addition, women with signs of depression or women who had a lower educational level were found to have lower self-efficacy compared to women with no signs of depression or women who had a higher educational level. The inconsistency in adherence to the intervention implementation probably contributed to its lack of effectiveness. This study serves as a starting point for further research, emphasizing the need for more robust research designs and improved implementation strategies to enhance effectiveness.

Ylipainoisten odottajien tukeminen puettavaa teknologiaa hyödyntävällä painonhallintainterventiolla Tutkimuksen tarkoituksena oli kehittää ja arvioida terveysteknologiaa hyödyntävä painonhallintainterventio ylipainoisille naisille raskausaikana ja synnytyksen jälkeen. Tutkimus toteutettiin kaksivaiheisena: kehittämis- ja toteutettavuusvaihe. Kehittämisvaihe sisälsi kaksi osatutkimusta. 1) Kuvailevassa monimenetelmätutkimuksessa selvitettiin äitiyshuollon ammattilaisten (n = 5) ja ylipainoisten raskaana olevien naisten (n = 11) painonhallinnan tukemiseen liittyviä käsityksiä. 2) Prospektiivisessa havainnointitutkimuksessa kuvattiin puettavaa teknologiaa hyödyntävän järjestelmän käytettävyyttä raskaana olevien naisten (n = 20) terveysparametrien jatkuvaan seurantaan. Kehittämisvaiheessa kerättyjen tietojen avulla mallinnettiin painonhallintainterventio ja toteutusstrategiat yhteistyössä äitiysneuvolan ammattilaisten ja ylipainoisten odottajien kanssa. Intervention keskeiset komponentit olivat 1) terveysteknologia, 2) motivoiva haastattelu, 3) tavoitteen asettelu ja 4) palaute. Tutkimuksen toisessa vaiheessa arvioitiin intervention toteutettavuutta kvasikokeellisella tutkimusmenetelmällä arvioimalla intervention vaikuttavuutta ylipainoisten odottajien (n = 54) syömisen ja liikunnan minäpystyvyyden lisäämiseen ja liiallisen raskaudenaikaisen painonnousun ehkäisemiseen. Lisäksi toteutettavuutta arvioitiin käyttöuskollisuuden, hyväksynnän ja intervention noudattamisen perusteella. Interventiolla ei ollut vaikutusta minäpystyvyyden muutokseen tai painonnousuun, johtuen todennäköisesti epäonnistuneesta implementaatiosta ja intervention vaihtelevasta hyödyntämisestä neuvolakäynneillä. Raskausajan painonnousun pysyminen suositusten mukaisena kuitenkin edisti synnytyksen jälkeistä painonhallintaa. Lisäksi havaittiin, että jo lievästi masennusoireiset tai alemman koulutustason omaavat naiset kokivat minäpystyvyyden matalammaksi verrattuna ei-masennusoireisiin tai korkeasti koulutettuihin naisiin. Tämä tutkimus toimii lähtökohtana jatkotutkimuksille, korostaen tarvetta vahvemmille tutkimusasetelmille ja tehokkaammille implementaatiostrategioille.